Speed of aging of populations by socioeconomics subgroups in China: A cross-sectional study of cognitive performance - P.M.M. Vicerra; J. Wu; Y. Wu (Elsevier, 2023)
Objectives: Although there is an association between socioeconomic factors and cognition, there are shortcomings in terms of examining the age of onset of decline between people with varying social backgrounds. This study aims to present the disparities in cognitive performance among older adults by simultaneously integrating health status, social characteristics, and age into an understandable metric. Study design: This study is cross-sectional. Methods: A sample of 3422 adults aged at least 60 was utilised from the 2015 wave of the China Health and Nutrition Survey to analyse the trajectories of cognitive ageing through the Characteristics approach. This approach generates an age-differential schedule whereby, as a hypothetical example, the cognition level Z of an individual aged 60 who has not completed schooling is demonstrated at age 66 by someone who has completed secondary schooling. Results: There was an increasing advantage with cognitive performance as the level of education completed increased; men aged 61.9 with a primary level of schooling and those aged 67.8 with postsecondary qualifications exhibit the same cognition performance as those aged 60 with no completed schooling. The observation also suggested that cognition advantages diminish through age. In terms of income, the age-differential schedule follows a similar pattern. albeit lower outcomes, to that of education differentials. Conclusion: When comparing education and income levels and their respective impacts on cognitive functioning, the former has been noted to have a larger effect. Education's effect has continuity in that it can influence opportunities until later ages.